A new species of Rhodacaroides (Mesostigmata: Ologamasidae) from Yintiaoling Nature Reserve, with a key to Rhodacaroides - Mu, Gui-Ming; Hou, Ze-Peng; Jin, Dao-Chao; Yi, Tian-Ci (Zootaxa, 2025)
A new species, Rhodcaroides multithornus Mu, Jin & Yi sp. nov. is described from litters of Yintiaoling National Nature Reserve, Chongqing, China. It can be distinguished from the other congeners by digit with 10–11 teeth fixed, two pairs of small and slender metapodal plates, and 11 pairs of dorsum setae slightly thorn. Additionally, a key to all species of Rhodcaroides is provided, based on characteristics of females.